2020
DOI: 10.5455/apd.114935
|View full text |Cite
|
Sign up to set email alerts
|

The relationships between personality disorders and early maladaptive schemas and the moderating role of gender

Abstract: Objective The aims of this study were to examine the relationship between personality disorders (PDs) and early maladaptive schemas, to determine the early maladaptive schemas that predict PDs, and to investigate the moderating role of gender in the relationship between PDs and early maladaptive schemas. Methods The sample consisted of 654 participants, 368 (56.4%) women and 286 (43.6%) men, aged 18–75 years, determined by the convenience sampling method. Data were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
8
0
1
Order By: Relevance
“…Relationships between EMS and mental health disorders have widely been studied, including substance and behavioural addictions, such as GD, interpersonal problems or depression, among others (Aloi et al, 2020 ; Bishop et al, 2022 ; Shorey et al, 2012 ). Of note is that women tend to experience higher levels of EMS than men (Bilge & Balaban, 2021 ; Janson et al, 2019 ). One of the dimensions of EMS related to GD is “Disconnection/Rejection”, which includes the schema of abandonment (Efrati et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Relationships between EMS and mental health disorders have widely been studied, including substance and behavioural addictions, such as GD, interpersonal problems or depression, among others (Aloi et al, 2020 ; Bishop et al, 2022 ; Shorey et al, 2012 ). Of note is that women tend to experience higher levels of EMS than men (Bilge & Balaban, 2021 ; Janson et al, 2019 ). One of the dimensions of EMS related to GD is “Disconnection/Rejection”, which includes the schema of abandonment (Efrati et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among the diagnostic criteria of histrionic personality disorder, there are desires to be the center of attention, to be appreciated and to be liked. These wishes are related to the fact that people always need the approval of others in order to feel valuable (Bilge & Balaban, 2021).…”
Section: Discussion Of the Relationship Between Early Maladaptive Sch...mentioning
confidence: 99%
“…It is seen that people who have distorted beliefs about relationships make wrong inferences when perceiving others and their relationships, and therefore experience SA (Çam & Çelik, 2018). This situation reaches visible dimensions in individuals with avoidant personality disorder (Bilge and Balaban, 2021) and borderline personality disorder (Faraji, 2021). Social isolation schema is formed as a result of exclusion and humiliation experiences in childhood (Roediger, 2020).…”
Section: Discussion Of the Relationship Between Early Maladaptive Sch...mentioning
confidence: 99%
“…Previous research demonstrated that personality and EMSs are related and can interact with each other in complex ways (Bilge & Balaban, 2021;Etemadnia et al, 2021;Güler & Özgörüş, 2022;Pauwels et al, 2016;Shojaati, Kalantari, & Mulavi, 2019;Shorey, Stuart, & Anderson, 2014;Stavropoulos et al, 2020;Thimm, 2011;Yığman et al, 2021). However, the relationship between these constructs still remains an area of ongoing research.…”
Section: Introductionmentioning
confidence: 99%